Exploring perceptions of dignity among older adults living in nursing homes: a qualitative study - Kejimu Sunzi; Hui Luo; Lina Yin; Yadi Li; Xin Zhou; Cheng Lei (Frontiers in Psychiatry)
BackgroundRapid global population ageing has significantly increased the number of older adults requiring institutional care. In nursing homes, older residents frequently experience reduced autonomy, diminished social status, and restricted opportunities for meaningful social engagement, all of which can severely threaten their sense of dignity. Although dignity is widely acknowledged as a fundamental human right and is critical for maintaining older adults’ psychological well-being and overall quality of life, limited attention has been paid to understanding how Chinese nursing-home residents perceive, experience, and preserve their dignity. Clarifying these dignity-related experiences is essential to inform interventions and policies aimed at improving care practices and enhancing residents’ quality of life.AimTo address the limited qualitative evidence on dignity in Chinese nursing homes, this study explored residents’ perceptions of dignity, the factors that undermine or enhance it, and the strategies they employ to preserve it.MethodsWe adopted a descriptive phenomenological design to explore nursing-home residents’ perspectives and lived experiences regarding dignity. Between June and December 2023, we conducted semi-structured interviews with 35 nursing-home residents in western China (aged 65–92 years; length of stay 1 to > 7 years). Purposive maximum-variation sampling captured diversity in age, gender, functional status, and socioeconomic background. All interviews were audio-recorded, transcribed verbatim, and thematically analyzed using Colaizzi’s phenomenological procedure. Reporting adhered to SRQR guidelines.ResultsThe following four themes were identified: Older people’s perception of dignity, The influence of dignity on the older people, Factors affecting the promotion of dignity, Dignity maintenance strategies for the older people.ConclusionDignity in nursing-home settings is deeply influenced by physical dependence, the quality of staff–resident interactions, and the availability of meaningful social engagement. When dignity is preserved, residents display better psychosocial adjustment; when violated, they experience significant emotional distress.RecommendationsNursing homes should implement staff training in person-centered, respect-focused care; design routines that maximize privacy and autonomy; and expand social and recreational programs. Future studies should develop and test targeted dignity-enhancement interventions and include family perspectives to create holistic, dignity-oriented care models.